Using the advantages and avoiding the risks – a public survey about the challenges of online purchases of medicines - Persson, A. ; 0000-0002-1829-1462; Troein, M. ; 0000-0001-6803-7545; Jakobsson, U. ; 0000-0003-3676-307X; Lundin, S. ; 0000-0003-0038-9661; Midlöv, P. ; 0000-0002-5871-8731; Lenander, C. (Scandinavian Journal of Primary Health Care, 2025)
Background: Around 95% of all websites selling medicines globally are illegal and contribute to the spread of substandard and falsified medicines. Hence, it is important to identify legal pharmacies when accessing medicines online. During 2022-2024, 250 million prescriptions were legally dispensed in Sweden, and 69% were prescribed in primary care. Pharmacists and general practitioners are key healthcare professionals who can guide people to safe online purchases. The overall aim was to describe Swedes' online purchasing habits for medicines. Methods: We used a cross-sectional design and collected information from the general population through an annual digital questionnaire for three years in a row, 2022-2024. In total, 6006 respondents, 18-79 years old, were included. Results: Fifty-two percent had bought medicines online in the last year. Most respondents, 91%, did not recognise the common EU logo mandatory for authorised online pharmacies. People buying over-the-counter medicines online were significantly younger than those buying prescription-only medicines online. Female gender and higher level of education were associated with more online purchases of medicines. Most respondents' purchasing habits were not influenced by external factors. Reasons for increased online purchases were, for example, that it helps planning regarding access to treatment. Conclusions: Half of the study participants have used online pharmacies, but fewer than 10% know how to identify a safe online pharmacy, i.e. many are at risk for fraud. Increasing this knowledge by informing those who prefer online purchases has the possibility to use the advantages and avoid the risks associated with online purchases of medicines.